Hypoxia and transforming growth factor‐beta1 pathway activation promote Chinese Hamster Ovary cell aggregation. Issue 4 (8th January 2018) - Qian, Yueming; Rehmann, Matthew S.; Qian, Nan‐Xin; He, Aiqing; Borys, Michael C.; Kayne, Paul S.; Li, Zheng Jian
Abstract: Suspension cultivation is the preferred mode of operation for the large‐scale production of many biologics. Chinese Hamster Ovary (CHO) cells are anchorage‐dependent in origin, but they have been widely adapted to suspension culture. In suspension culture, formation of CHO cell aggregates is a common phenomenon and compromises cell culture performance in multiple ways. To better understand the underlying mechanisms that regulate cell aggregation, we utilized CHO‐specific transcriptome profiling as a screening tool and demonstrated that many genes encoding extracellular matrix (ECM) proteins were upregulated in the cultures with increased cell aggregation. Significantly, hypoxia was identified to be a cause for promoting CHO cell aggregation, and transforming growth factor beta1 (TGFβ1) pathway activation served as an intermediate step mediating this biological cascade. These transcriptomics findings were confirmed by cell culture experiments, and it was further demonstrated that adding recombinant TGFβ1 to the culture significantly increased ECM protein fibronectin expression and cell aggregation. The results of this study emphasize the importance of adequate mixing and oxygen supply for suspension cultures from a new angle, and regulating the TGFβ1 pathway is proposed as a new strategy for mitigating cell aggregation to improve cell culture performance. Abstract : Hypoxia has been identified to be a cause for promoting CHO cell aggregation. Hypoxic conditions increase TGF‐beta production and activate its pathway, leading to increased production of extracellular matrix proteins. Extracellular matrix proteins in turn form networks gathering the cells.